Gambaran Pengetahuan Masyarakat Terhadap Pelayanan Gizi Berbasis Gen Dalam Pencegahan Penyakit Tidak Menular di Indonesia: Gambaran Pengetahuan Masyarakat Terhadap Pelayanan Gizi Berbasis Gen dalam Pencegahan Penyakit Tidak Menular di Indonesia - Wulandari, Fatma Annisa; Aji, Arif Sabta; Afifah, Effatul; Paramashanti, Bunga Astria; Listiyana, Fani; Khouridhiya, Mumtaz; Surendran, Shelini (Universitas Airlangga, 2023)
Background: Non-Communicable Diseases (NCDs) are the primary health issues in Indonesia, with their prevalence increasing each year. The advancement of technology, such as gene-based nutrition services, could offer an alternative approach to prevent NCDs in the present and future. Objectives: This study aims to assess the current level of knowledge regarding gene-based nutrition services among Indonesians for NCD prevention. Methods: A qualitative phenomenological study was conducted across five provinces in Indonesia. In-depth interviews were conducted with ten informants, selected using the snowball sampling technique. The research focused on themes such as understanding gene-based nutrition services, genetic knowledge, and the role of gene-based nutritional analysis in NCD prevention. Thematic analysis was performed using NVivo v.14. Results: The community demonstrated a solid grasp of the concept of genetics and inherited traits. However, they struggled with genetic terminology. Most Indonesians had limited awareness of gene-based nutrition services, although they recognized their benefits in disease detection and dietary management. They also knew that the cost of this inspection was expensive, and individuals expressed concerns about the potential implications of disease risk detection. Participants notably clarified that NCDs are not communicable diseases and can be prevented through gene-based nutritional interventions. Interest in gene-based nutrition services was substantial, yet barriers included cost and facility accessibility. Conclusions: Indonesians generally possess limited knowledge about genetics, gene-based nutrition services, and genetic testing. However, they acknowledge the significance of genetic-based nutrition services in early NCD prevention, as these services can help determine appropriate dietary patterns and lifestyles.